THE EFFECT OF EMOTIONAL DEMONSTRATION METHODS AND VIDEO LEARNING ON HAND WASHING ON KNOWLEDGE AND SKILLS OF HOUSEWIVES - Winda Triana; Ervon Verza; Pahrur Razi (OPI Napoli, 2021)
Introduction: Efforts to prevent the transmission of infectious diseases through hands can be prevented by washing hands. It is especially emphasized on mothers with toddlers. However, many mothers do not know how to wash their hands using soap correctly and adequately. This study aims to analyze the effect of the emotional demonstration method and video media on how to wash hands on the knowledge and skills of homemakers. Materials and Methods: This research is a quasi-experimental method, with a two-group design pretest-posttest approach involving 40 participants, conducted in September-October 2020 in Penyengat Olak Village. The research sample was divided into two groups, 20 participants received the emo demo method, and 20 other participants received videos. Results: The results showed an increase in mothers' knowledge and skills after receiving an education using the emotional demonstration method and video media and statistically showed significant results (<0.05). Conclusion: Therefore, this educational media is highly recommended as a method of educating the public about good and correct hand washing